KIF5A and ALS2 Variants in a Family With Hereditary Spastic Paraplegia and Amyotrophic Lateral Sclerosis - Simone, Marta; Trabacca, Antonio; Panzeri, Elena; Losito, Luciana; Citterio, Andrea; Bassi, Maria Teresa (Frontiers in Neurology, 2018)
Missense mutations within the kinesin family member 5A gene (KIF5A) are a known cause of a dominant form of hereditary spastic paraparesis (spastic paraplegia type 10- SPG10, OMIM: 604187) and of Charcot-Marie-Tooth disease type 2 (CMT2). Mutations in ALS2, the gene coding for alsin protein, have been demonstrated to be associated with a spectrum of rare autosomal recessive disorders including infantile ascending hereditary spastic paralysis (IAHSP), juvenile primary sclerosis (JPLS) with retrograde degeneration of the upper motor neurons, and juvenile ALS with involvement of both upper and lower motor neuron involvement. In this paper we describe a family in which the proband, a 14-year-old boy started manifesting an early onset (age 14 months) pure form of HSP rapidly progressing to a juvenile form of ALS. This boy carries a heterozygous missense variant in KIF5A, inherited from the father, and a homozygous missense variant in ALS2. The father, with family history of ALS, in the last few years has been developing signs and symptoms of affection of both the upper and lower motor neuron systems, with mild bulbar motor involvement and emotional lability. The patients described in this family, confirm the continuum and partial overlap of the two clinical entities, HSP and ALS, historically viewed as distinct entities. The genetic findings in this family further substantiate the genetic bases underlying the overlap, broadening the clinical spectrum associated with KIF5A mutations.